Length-weight relationship and relative condition factor of two dominant species (Cyclocheilithys apogon and Notopterus notopterus) at Subang Lake, Selangor, Malaysia - Xeai, Li Chai; Hashim, Rohasliney; Rahmat, Muhammad Nur Aiman; Kamaludin, Hamizan; Habullah, Nur Ain; Kamaruddin, Izharuddin Shah (Universiti Putra Malaysia Press, 2021)
Length-weight relationships and relative condition factors were conducted to provide information on fish species’ growth conditions and general well-being in the freshwater habitat. This study was conducted using fish as a bioindicator for the health of the ecosystem. Cyclocheilithys apogon (Beardless barb) and Notopterus notopterus (Bronze featherback) are the most dominant species in Subang Lake. A four-month sampling was conducted to collect the sample of Beardless barb and Bronze featherback. A total of 422 individuals of Beardless barb and 344 individuals of Bronze featherback were measured and weighed. The mean total length of Breadless barb was 13.11 ± 1.31 cm with the mean weight of 31.88±9.93 g. The mean of the total length and weight of Bronze featherback was 16.05 ± 2.07 cm and 30.38 ± 15.63 g. Both fish species showed negative allometric growth with the exponent b value 2.884 and 2.886, respectively. The condition factor of Beardless barb (1.184 ± 0.134) and Bronze featherback (1.010 ± 0.163) obtained from this study reflects a fair growth condition based on K value by Barnham & Baxter (2003). Further studies need to be conducted to determine the significant impacts that affect fish species’ growth conditions.